Delineation of ISEcp1 and IS26-Mediated Plasmid Fusion Processes by MinION Single-Molecule Long-Read Sequencing - Chen, Kaichao; Xie, Miaomiao; Chan, Edward Wai-Chi; Chen, Sheng (Frontiers in Microbiology, 2022)
We recently reported the recovery of a novel IncI1 type conjugative helper plasmid which could target mobile genetic elements (MGE) located in non-conjugative plasmid and form a fusion conjugative plasmid to mediate the transmission of the non-conjugative plasmid. In this study, interactions between the helper plasmid pSa42-91k and two common MGEs, ISEcp1 and IS15DI, which were cloned to pBackzero vector, were monitored during the conjugation process to depict the molecular mechanisms underlying the plasmid fusion process mediated by IS elements. The MinION single-molecule, long-read sequencing technology can dynamically reveal the plasmid recombination events and produce valuable information on genetic polymorphism and plasmid heterogeneity in different MDR-encoding bacteria; such data should facilitate development of new strategies to control evolution and dissemination of MDR plasmids